Amine-modified Ni-DOBDC MOF for CO2 capture: CO2 adsorption capacity and reusability - Fahriansyah, Irsan; Khatrin, Irena; Abdullah, Iman; Krisnandi, Yuni Krisyuningsih (Environmental and Materials, 2024)
Background: Anthropogenic carbon dioxide (CO₂) emissions have risen significantly due to the extensive use of fossil fuels, necessitating the development of effective CO₂ capture and conversion techniques. Adsorption using Metal-Organic Frameworks (MOFs) has shown great potential due to their high CO₂ adsorption capacity, particularly Ni-based MOFs. Enhancing their adsorption efficiency remains a key research focus to improve sustainability in CO₂ capture applications. Methods: Ni-based MOF (Ni-DOBDC) was synthesized using the solvothermal method, employing DMF as the solvent and 2,5-dihydroxyterephthalic acid (DOBDC) as the organic ligand. To enhance CO₂ adsorption capacity, Ni-DOBDC was further modified with ethylenediamine (EDA) via post-synthetic modification. Structural characterization was performed using XRD, confirming similarity to the Ni-DOBDC reference (CCDC 288477), and FTIR, which showed enhanced absorbance peaks. SEM-EDX analysis revealed a flower-like morphology with an average particle size of 0.75 μm. CO₂ adsorption tests were conducted on Ni-DOBDC and EDA/Ni-DOBDC (10%) using the titration method under controlled conditions. Findings: The CO₂ adsorption capacity of Ni-DOBDC and EDA/Ni-DOBDC was tested at 70°C with a CO₂ concentration of 50% in N₂. EDA modification significantly improved CO₂ adsorption capacity, with EDA/Ni-DOBDC achieving 9.95 mmol g⁻¹ compared to pristine Ni-DOBDC’s 6.44 mmol g⁻¹. However, Ni-DOBDC exhibited better regeneration ability in a three-cycle reusability test, likely due to EDA leaching during regeneration. Conclusion:  EDA-modified Ni-DOBDC demonstrates enhanced CO₂ adsorption capacity, making it a promising material for CO₂ capture applications. However, its reduced regeneration stability suggests the need for further optimization to improve long-term performance. Future studies should explore strategies to minimize EDA leaching while maintaining high adsorption efficiency. Novelty/Originality of this article: This study provides new insights into improving Ni-based MOF performance for CO₂ capture through post-synthetic modification with EDA. The findings highlight a trade-off between increased adsorption capacity and material stability, emphasizing the need for further refinement in MOF functionalization strategies.